THE EFFECT OF USING GEOGEBRA ON MIDDLE SCHOOL STUDENTS' UNDERSTANDING OF CONCEPTS IN THE MATERIAL OF TWO-VARIABLE LINEAR EQUATION SYSTEMS (SPLDV) - Aqfi, Farizi; Siregar, Machrani Adi Putri (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study aims to determine the effect of using the GeoGebra application on junior high school students' understanding of mathematical concepts in the topic of Two-Variable Linear Equations Systems (SPLDV). The type of research used is a quasi-experiment with a posttest-only control group design. The population of this study is all eighth-grade students at SMP Islam Terpadu Al-Fakhri, while the sample consists of two classes selected through purposive sampling, namely class VIII-B as the experimental class receiving instruction using GeoGebra and class VIII-A as the control class with conventional teaching methods. The research instrument consisted of a written test totaling 6 questions that had been tested for validity and reliability. The research data were analyzed using a t-test with a significance level of 0.05. The research results show that there is a difference in conceptual understanding between students who learn using GeoGebra and students who learn through conventional learning. The average post-test score of the experimental class was 19.46, higher than the control class at 15.78, with standard deviations of 3.12 and 4.34, respectively. Based on these analysis results, it can be concluded that the use of GeoGebra has a positive effect on improving students' understanding of mathematical concepts in the SPLDV material.